Reframing Gen-Z Engagement in Islamic Higher Education: Integrating Islamic Values into Co-Curricular Frameworks in the Digital Era - Yusnaini Yusnaini; Nuriman; Setiawan (ABANNA: Journal Of Contemporary Islamic Education, 2025)
This study critiques the digitalization gap in education, focusing on the neglect of extracurricular activities and the integration of Islamic values. While digital reforms enhance administrative efficiency and curriculum design, they often sideline activities that foster holistic student engagement. Platforms like SIAKAD and EdLink offer limited support for extracurricular programs, reducing Gen-Z’s exposure to interactive, value-based environments. A qualitative case study at IAIN Langsa, Lhokseumawe, and Takengon highlights the insufficient incorporation of Islamic values in co-curricular frameworks. Data from focus group discussions and interviews with stakeholders, lecturers, and students reveal logistical challenges and institutional resistance as key barriers. Misalignment with Gen-Z’s preference for integrated learning—combining spirituality, social justice, and career readiness—underscores the need for reform. Critiquing conventional engagement theories, the study proposes a new model rooted in Islamic principles to bridge theoretical gaps and promote holistic, meaningful student development in Islamic higher education.